Pemimpin Yang Tangguh dan Bertanggungjawab pada Masa Krisis: Tafsir Kitab 1 Samuel 22:1-5 - Agustinus Gulo; Artariah Artariah; Herdiana Sihombing (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This paper discusses the characteristics and responsibilities of leaders in the context of the uncertainty that often occurs during crises. The purpose of this research is to gain an understanding of the duties of a person who has the ability to lead and direct his followers. Being a leader must have behavior in performing each task. In this study, the author analyzes and interprets the text from the Bible 1 Samuel 22:1-5. This book tells about the leadership of David who fled and hid from the pursuit of King Saul. In leadership, David became a tough, responsible leader. Even though David was on the run, he still did his duty to help those who were weak and did not look down on them. David was a responsible leader who was able to provide direction, stability, and make wise decisions during difficult times.